THE SERBIAN ECONOMY TEN YEARS AFTER THE GLOBAL ECONOMIC CRISIS - Uvalić, Milica; Cerović†, Božidar; Atanasijević, Jasna (Economic Annals, 2020)
The global financial crisis hit the Serbian economy severely in late 2008. The subsequent decade has been characterized by negative or very modest economic growth and Serbia is now just slightly above the development level of ten years ago. This paper analyses the most im-portant economic milestones during this decade and investigates why only modest progress has been made, despite various measures implemented by the Serbian gov-ernment. It examines the background to Serbia’s delayed transition and analyses the effects of the global economic crisis on the Serbian economy. It outlines the policy re-sponses and their results, focusing on public finance, foreign trade, reindustrialisation, FDI, the labour market, and sources of growth. The paper sets out the key challeng-es to accelerating Serbia’s economic growth and identifies the main elements of a new long-term development strategy.